Scottish Health Technologies Group: enhancing patient engagement. (20th January 2021) - Stewart, James Angus; Clifton, Edward; Macpherson, Karen; Angelova, Nikolina; Morrison, Graeme
Abstract: Objectives: The Scottish Health Technologies Group (SHTG) provides evidence support and advice to the National Health Service in Scotland on the use of new and existing health technologies, which, although not medicines, are likely to have significant implications for people's care. The purpose of this paper is to highlight the developments that have taken place in the SHTG's patient involvement processes in the years 2017 to 2019, focusing primarily on specific engagement with patient organizations and considering how the new approaches have been received by stakeholders. Methods: Feedback from patient organizations that participated in the SHTG submission process, alongside SHTG committee members' views on patient organizations contributions, was gathered primarily via online questionnaires. The number of times that patient organizations were invited and accepted the opportunity to peer-review SHTG advice statements prior to and after the employment of a Public Involvement Advisor (PIA) was analyzed. Results: Completed questionnaires ( n = 4) from three case study examples showed high patient organization satisfaction with their experience of the SHTG process. The feedback from SHTG committee members that was gathered indicated that patient organization participation was generally well received. The number of peer reviews from patient organizations for SHTG advice statements in 2018–2019 doubled to 86 percent of the total advice statements ( n = 22), compared with 43 percent ( n = 14) in 2016–2017. Conclusions: Significant progress has been made toward improving the SHTG's patient involvement processes. A dedicated PIA post within the SHTG has allowed for a more tailored support to patient organizations and has encouraged their increased participation in SHTG processes.